PLT antigen discrepancy pattern among couples with recurrent abortion - Shad, Ghazal Ahmadzadeh; Ghasemi, Ali; Zadsar, Maryam; Shaeigan, Mojgan; Samiee, Shahram; Zare, Ahad (Frontiers in Medicine, 2024)
Background: Recurrent abortion refers to a condition of two or more consecutive pregnancies without known etiology affected by miscarriage before the completion of 20 th weeks of gestational age. However, several hypotheses have been proposed but not much data are available concerning the relationship between human platelet antigens (HPAs) polymorphisms and recurrent abortion. This study was conducted to evaluate the genetic difference of HPA-1, -2, -3, -5, and -15 in Iranian couples with a history of recurrent abortion.In this cross-sectional study, a total of 74 couples with at least 2 recurrent abortions without any known specified causes enrolled in the study. HPAs polymorphisms genotyping were performed by Single Specific Primer PCR. genotype frequency was calculated using the Hardy Weinberg equation.A total of 39 couples (52.7%) had HPA genotyping partial mismatches. The most common partial mismatch pairs were found concomitantly on both HPA-15a and HPA-15b in three couples (4%), followed by two (2.7%) on HPA-3a, and one (1.3%) in each HPA-2b and HPA-5b. There was a deviation from Hardy-Weinberg equilibrium in the HPA-2 & -5 systems Conclusions: Present study declared that partial mismatches of HPA-3 & -15 genotypes were common among Iranian couples by the history of recurrent abortion and approximately half of the couples carried at least one HPA gene, that was absent on their partners. Further studies might be helpful to clarify the association between HPAs polymorphisms and recurrent abortion such as investigation about the alloantibodies against HPAs.